Translation and validation of the new version of the Knee Society Score – The 2011 KS Score – into Brazilian Portuguese() - Silva, Adriana Lucia Pastore e (Rev Bras Ortop, 2017)
OBJECTIVE: Translation, cultural adaptation, and validation of the new version of the Knee Society Score – The 2011 KS Score – into Brazilian Portuguese and verification of its measurement properties, reproducibility, and validity. In 2012, the new version of the Knee Society Score was developed and validated. This scale comprises four separate subscales: (a) objective knee score (seven items: 100 points); (b) patient satisfaction score (five items: 40 points); (c) patient expectations score (three items: 15 points); and (d) functional activity score (19 items: 100 points). METHOD: A total of 90 patients aged 55–85 years were evaluated in a clinical cross-sectional study. The pre-operative translated version was applied to patients with TKA referral, and the post-operative translated version was applied to patients who underwent TKA. Each patient answered the same questionnaire twice and was evaluated by two experts in orthopedic knee surgery. Evaluations were performed pre-operatively and three, six, or 12 months post-operatively. The reliability of the questionnaire was evaluated using the intraclass correlation coefficient (ICC) between the two applications. Internal consistency was evaluated using Cronbach's alpha. RESULTS: The ICC found no difference between the means of the pre-operative, three-month, and six-month post-operative evaluations between sub-scale items. CONCLUSION: The Brazilian Portuguese version of The 2011 KS Score is a valid and reliable instrument for objective and subjective evaluation of the functionality of Brazilian patients who undergo TKA and revision TKA.